Evidence for Prohypertensive, Proinflammatory Effect of Interleukin-10 During Chronic High Salt Intake in the Condition of Elevated Angiotensin II Level. Issue 4 (October 2017) - Singh, Purnima; Castillo, Alexander; Islam, M. Toriqul; Majid, Dewan S.A.
Abstract : IL-10 (interleukin-10) has been suggested to play a protective role in angiotensin II (AngII)–induced cardiovascular disorders. This study examined the role of endogenous IL-10 in salt-sensitive hypertension and renal injury induced by AngII. Responses to chronic AngII (400 ng/min per kilogram body weight; osmotic minipump) infusion were evaluated in IL-10 gene knockout mice fed with either normal salt diet (0.3% NaCl) or high salt (HS; 4% NaCl) diet, and these responses were compared with those in wild-type mice. Normal salt diets or HS diets were given alone for the first 2 weeks and then with AngII treatment for an additional 2 weeks (n=6 in each group). Arterial pressure was continuously monitored by implanted radio-telemetry, and a 24-hour urine collection was performed by metabolic cages on the last day of the experimental period. Basal mean arterial pressure was lower in IL-10 gene knockout mice than in wild-type (98±3 versus 113±3 mm Hg) mice. Mean arterial pressure responses to normal salt/HS alone or to the AngII+normal salt treatment were similar in both strains. However, the increase in mean arterial pressure induced by the AngII+HS treatment was significantly lower in IL-10 gene knockout mice (15±5% versus 37±3%) compared with wild-type mice. Renal tissue endothelial nitric oxide synthase expression (≈3-folds) and urinary excretion of nitric oxide metabolites, nitrate/nitrite (1.2±0.1 versus 0.2±0.02 µmol/L/24 hours) were higher in IL-10 gene knockout mice compared with wild-type mice. These results indicate that an increase in nitric oxide production helps to mitigate salt-sensitive hypertension induced by AngII and suggest that a compensatory interaction between IL-10 and nitric oxide exists in modulating AngII-induced responses during HS intake. Abstract : Supplemental Digital Content is available in the text.